PENERAPAN STRATEGI THINK TALK WRITE DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IXD SMP NEGERI 10 TAPUNG - Sinaga, Yohana S; Hutapea, Nahor Murani; ', Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is based on problems of learning process in the class IXD SMP Negeri 10 Tapung which is teacher-centered, less students are given the opportunity to actively participate in building their own knowledge affecting low student’s mathematics achievement. From the test of results obtained in similarity and congruence main topic just 8 students (33,33%) who achieve minimum mastery criteria (KKM). This research is classroom action research that aimed of this to improve learning process and increase students’ math achievement at class, through the implementation of think talk write strategy in cooperative learning. The subject of this research are 24 people, there are 12 boys and 12 girls with the heterogenous level. The instruments of data collection were observation sheets and mathematics achivement tests. Teacher and student activity’s data were analyzed with qualitative descriptive and mathematical understanding ability data were analyzed with quantitative descriptive. Based on data’s analyz can be concluded that the implementation of think talk write strategy in cooperative learning can improve the learning process and increase students’ math achievement at class SMP Negeri 10 Tapung of first semester 2015/2016 of geometry with curved side on main topic.Key Word : Students’ math Achievement, Think Talk Write Strategy In Cooperative Learning, Classroom Action Research.